Glucopyranosyl Lipid Adjuvant (GLA), a Synthetic TLR4 Agonist, Promotes Potent Systemic and Mucosal Responses to Intranasal Immunization with HIVgp140 - Arias,MA; Van,Roey GA; Tregoning,JS; Moutaftsi,M; Coler,RN; Windish,HP; Reed,SG; Carter,D; Shattock,RJ (PLOS One, 2012)
Successful vaccine development against HIV will likely require the induction of strong, long-lasting humoral and cellularimmune responses in both the systemic and mucosal compartments. Based on the known immunological linkage betweenthe upper-respiratory and urogenital tracts, we explored the potential of nasal adjuvants to boost immunization for theinduction of vaginal and systemic immune responses to gp140. Mice were immunized intranasally with HIV gp140 togetherwith micellar and emulsion formulations of a synthetic TLR4 agonist, Glucopyranosyl Lipid Adjuvant (GLA) and responseswere compared to R848, a TLR7/8 agonist, or chitosan, a non TLR adjuvant. GLA and chitosan but not R848 greatlyenhanced serum immunoglobulin levels when compared to antigen alone. Both GLA and chitosan induced high IgG andIgA titers in nasal and vaginal lavage and feces. The high IgA and IgG titers in vaginal lavage were associated with highnumbers of gp140-specific antibody secreting cells in the genital tract. Whilst both GLA and chitosan induced T cellresponses to immunization, GLA induced a stronger Th17 response and chitosan induced a more Th2 skewed response. Ourresults show that GLA is a highly potent intranasal adjuvant greatly enhancing humoral and cellular immune responses,both systemically and mucosally.